2018
DOI: 10.21315/mjms2018.25.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Modulation After Two Different Repetitive Transcranial Magnetic Stimulation Protocols in Similar Ischemic Stroke Patients

Abstract: BackgroundStroke is one of the leading causes of mortality and morbidity in Malaysia. Repetitive transcranial magnetic stimulation (rTMS) is one of the new non-invasive modality to enhance the motor recovery in stroke patients.ObjectivesThis pilot study compared the motor evoked potential (MEP) changes using different settings of rTMS in the post-ischemic stroke patient. The goal of the study is to identify effect sizes for a further trial and evaluate safety aspects.MethodsEight post-stroke patients with uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Conversely, the MEP amplitude of the unaffected M1 decreased by 21.29% (95% CI = − 27.17% to − 15.41%, p < 0.001, I 2 = 56.88%) immediately after a single session of LF-rTMS, in line with two other studies [ 41 , 42 ]; however, the publication bias was significant (p = 0.040). Likewise, the MEP amplitude of the unaffected M1 decreased after multiple sessions of LF-rTMS (Hedges’ g = − 0.54, 95% CI = − 0.78 to − 0.30, p < 0.001, I 2 = 26.05%), with no significant publication bias identified (p = 0.502).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Conversely, the MEP amplitude of the unaffected M1 decreased by 21.29% (95% CI = − 27.17% to − 15.41%, p < 0.001, I 2 = 56.88%) immediately after a single session of LF-rTMS, in line with two other studies [ 41 , 42 ]; however, the publication bias was significant (p = 0.040). Likewise, the MEP amplitude of the unaffected M1 decreased after multiple sessions of LF-rTMS (Hedges’ g = − 0.54, 95% CI = − 0.78 to − 0.30, p < 0.001, I 2 = 26.05%), with no significant publication bias identified (p = 0.502).…”
Section: Resultssupporting
confidence: 87%
“…The effects after a single session and multiple sessions of LF-rTMS were evaluated by 11 [ 9 , 24 26 , 28 , 31 , 32 , 34 , 36 , 41 , 42 ] and 24 [ 44 , 46 , 47 , 49 51 , 54 – 60 , 62 , 63 , 65 , 67 71 , 74 , 76 , 78 ] studies, respectively. Dos Santos et al found that 10 sessions of LF-rTMS increased the cortical excitability of the unaffected M1, measured using an intensity tracking measuring approach that the intensity inducing MEPs of 1 mV by a single-pulse TMS stimulation was determined in the study to represent corticospinal excitability [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations